Planning of Primary School Education in Nigeria: Problems and Way Forward - Hayab Fortune Josiah; Ogunode Niyi Jacob (Research Parks Publishing LLC, 2021)
Primary school education in Nigeria is design to give the post-nursery education for children aged 6-11. The primary school education had been described as the foundational education that laid the foundation for other educational system. The primary school education is beset with many problems. Poor planning is one of the major problem facing the primary school education in Nigeria. This article discusses the problems facing the planning of primary school education in Nigeria. The article identified;inadequate planning fund, shortage of professional planners with specialization in primary school planning, shortage of data, corruption, political instability, poor capacity development of planners, policies instability, inadequate planning tools and political influence as the problems facing the planning of primary schools education in Nigeria. In order to solve these problems, this article offers the following recommendations: adequate funding of planning of public primary schools, employment of professional planners, provision of materials, generation of current educational data, political stability, policy stability and corruption should be fought in the ministries and agencies of education.